Antibacterial and photodynamic effects of some plant extracts for cavity disinfection - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (ELSEVIER, 2019)
Background: In current dental treatments, with the aim of a preventive approach,it is argued that removing only the infected layer of dentin is sufficient for cavity preparation. However it is impossible to be sure that the infected layer was completely removed. In addition, the cause of secondary caries and post operative sensitivities has been reported as residual bacteria in some studies. The aim of this study is to investigate the antibacterial and photo-active properties of Cotinus coggygria Scop., Rumex cristatus DC., Beta vulgaris L.var.cicla and Eruca sativa aqueous extracts, and to investigate their usefulness for cavity disinfection in dentistry. Method: The aqueous solutions of plant extracts were prepared to be at a maximum concentration and the Streptococcus mutans solutions mixed with phosphate buffered saline to give 10(8) cfu/mL. A 430-480 nm wavelength light source was used for the irradiation. Three different applications were made: extract + Streptococcus mutans mixture exposed to ligh; extract + Streptococcus mutans mixture that was not exposed to light and S. mutans exposed to light. Results: No antibacterial effect was found for the second and third applications. In the first application, however, irradiation with extract + Streptococcus mutans mixture reduced the number of microorganisms in the beginning by 99% for only Rumex cristatus DC. extract (log 2). Conclusion. Rumex cristatus DC. extract can be used as art alternative in photo-active disinfection of cavities in dentistry.
Keywords: Plant extracts; Antibacterial; Photo-active; Cavity disinfection; Dentistry; Antimicrobial photodynamic therapy; ANTIMICROBIAL ACTIVITY; STREPTOCOCCUS-MUTANS; IN-VITRO; ANTIOXIDANT; THERAPY; PHOTOSENSITIZERS; IMPACT; CICLA; VIVO